One Dog Night : Andy Carpenter #9 - Rosenfelt, David (New York : Minotaur Books, 2011)
Defense lawyer Andy Carpenter takes on a cold case when the suspected murderer turns out to be the man who saved his beloved dog.
"An Andy Carpenter mystery"--Jacket.
Keywords: Carpenter, Andy (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; New Jersey -- Fiction; Mystery fiction; Legal fiction